Global vegetation zonation and terrestrial climate of the warm Early Eocene - Nick Thompson; Ulrich Salzmann; David K. Hutchinson; Stephanie L. Strother; Matthew J. Pound; Torsten Utescher; Julia Brugger; Thomas Hickler; Emma P. Hocking; Daniel J. Lunt (Earth-Science Reviews, 2025)

Genomic evaluation of mud sunfish in the atlantic slope drainage - Stephen Knott; Richard Raesly; Daniel Hocking; Jay Stauffer; Amy Welsh (Fisheries Research, 2024)

Shelf break exchange processes influence the availability of the northern shortfin squid, Illex illecebrosus , in the Northwest Atlantic - Sarah L. Salois; Kimberly J. W. Hyde; Adrienne Silver; Brooke A. Lowman; Avijit Gangopadhyay; Glen Gawarkiewicz; Anna J. M. Mercer; John P. Manderson; Sarah K. Gaichas; Daniel J. Hocking; Benjamin Galuardi; Andrew W. Jones; et al. (Fisheries Oceanography, 2023)
The United States Northern Shortfin squid fishery is known for its large fluctuations in catch at annual scales. In the last 5 years, this fishery has experienced increased availability of Illex illecebrosus along the Northeast US continental shelf (NES), resulting in high catch per unit effort (CPUE) and early fishery closures due to quota exceedance. The fishery occurs within the Northwest Atlantic, whose complex dynamics are set up by the interplay between the large‐scale Gulf Stream, mesoscale eddies, Shelfbreak Jet, and shelf‐slope exchange processes. Our ability to understand and quantify this regional variability is requisite for understanding the availability patterns of Illex , which are largely influenced by oceanographic conditions. In an effort to advance our current understanding of the seasonal and interannual variability in this species' relative abundance on the NES, we used generalized additive models to examine the relationships between the physical environment and hotspots of productivity to changes in CPUE of I. illecebrosus in the Southern stock component, which comprises the US fishery. Specifically, we derived oceanographic indicators by pairing high‐resolution remote sensing data and global ocean reanalysis physical data to high‐resolution fishery catch data. We identified a suite of environmental covariates that were strongly related to instances of higher catch rates. In particular, bottom temperature, warm core rings, subsurface features, and frontal dynamics together serve as indicators of habitat condition and primary productivity hotspots, providing great utility for understanding the distribution of Illex with the potential for forecasting seasonal and interannual availability.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Demographic effects of phenological variation in natural populations of two pond-breeding salamanders - Thomas L. Anderson; Julia E. Earl; Daniel J. Hocking; Michael S. Osbourn; Tracy A. G. Rittenhouse; Jarrett R. Johnson (Oecologia, 2021)

Predicted alteration of surface activity as a consequence of climate change - Meaghan R. Gade; Grant M. Connette; John A. Crawford; Daniel J. Hocking; John C. Maerz; Joseph R. Milanovich; William E. Peterman (Ecology, 2020)
Wildlife are faced with numerous threats to survival, none more pressing than that of climate change. Understanding how species will respond behaviorally, physiologically, and demographically to a changing climate is a cornerstone of many contemporary ecological studies, especially for organisms, such as amphibians, whose persistence is closely tied to abiotic conditions. Activity is a useful parameter for understanding the effects of climate change because activity is directly linked to fitness as it dictates foraging times, energy budgets, and mating opportunities. However, activity can be challenging to measure directly, especially for secretive organisms like plethodontid salamanders, which only become surface active when conditions are cool and moist because of their anatomical and physiological restrictions. We estimated abiotic predictors of surface activity for the seven species of the Plethodon jordani complex. Five independent data sets collected from 2004 to 2017 were used to determine the parameters driving salamander surface activity in the present day, which were then used to predict potential activity changes over the next 80 yrs. Average active seasonal temperature and vapor pressure deficit were the strongest predictors of salamander surface activity and, without physiological or behavioral modifications, salamanders were predicted to exhibit a higher probability of surface activity during peak active season under future climate conditions. Temperatures during the active season likely do not exceed salamander thermal maxima to cause activity suppression and, until physiological limits are reached, future conditions may continue to increase activity. Our model is the first comprehensive field‐based study to assess current and future surface activity probability. Our study provides insights into how a key behavior driving fitness may be affected by climate change.

Methylmercury Bioaccumulation in an Urban Estuary: Delaware River, USA - Kate Buckman; Vivien Taylor; Hannah Broadley; Daniel Hocking; Prentiss Balcom; Rob Mason; Keith Nislow; Celia Chen (Estuaries and Coasts, 2017)

Abundance and phenology patterns of two pond-breeding salamanders determine species interactions in natural populations - Thomas L. Anderson; Daniel J. Hocking; Christopher A. Conner; Julia E. Earl; Elizabeth B. Harper; Michael S. Osbourn; William E. Peterman; Tracy A. G. Rittenhouse; Raymond D. Semlitsch (Oecologia, 2015)

Influence of agricultural upland habitat type on larval anuran assemblages in seasonally inundated wetlands - Kimberly J. Babbitt; Matthew J. Baber; Daniel L. Childers; Daniel Hocking (Wetlands, 2009)